PROBLEMS OF THE LEGALITY OF THE USE OF TECHNICAL EQUIPMENT DURING CRIMINAL INTELLIGENCE - Tarasevičius, Petras (Teisė, 2017)
The article presents the analysis of the juridical preconditions of the use of technical equipment during criminal intelligence. The problems of the distinguishing the use of technical equipment by general procedure and the use of technical equipment according to special procedure provided by the Law of the criminal intelligence of the Republic of Lithuania are being analysed as well.